Penetapan Ahli Waris Secara Kontensius Akibat Salah Satu Ahli Waris Mafqud dalam Perspektif Kompilasi Hukum Islam - Alfi Karomah; Abd. Rouf (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
The determination of heirs constitutes a fundamental prerequisite for the administration of inheritance under Indonesian Islamic inheritance law. Nevertheless, the procedural law governing the Religious Courts has not specifically regulated the determination of heirs involving a mafqud (a missing heir whose existence or whereabouts remain unknown), creating a normative gap that affects judicial practice and legal certainty. This study aims to analyze the legal basis for applying contentious proceedings in determining the legal status of a mafqud heir, examine the judges' legal reasoning, and evaluate the legal consequences of the decision for the civil rights of the missing heir. Employing a normative legal research method through statutory, case, and conceptual approaches, this study uses the Decision of the Surabaya Religious Court Number 0456/Pdt.G/2026/PA.Sby as the primary object of analysis. The findings indicate that contentious proceedings function as a procedural solution to address the absence of specific procedural rules concerning mafqud heirs. The judges relied on Article 49(b) of the Religious Courts Law and Articles 171(c) and 174(1) of the Compilation of Islamic Law in affirming the respondent's status as a lawful heir based on a blood relationship. Although the decision provides legal certainty for the existing heirs and safeguards the civil rights of the mafqud heir, it does not regulate the administration of the missing heir's inheritance share, thereby leaving potential legal uncertainty should the heir subsequently reappear. Accordingly, this study recommends reforming the procedural law of the Religious Courts by introducing explicit provisions concerning the determination of mafqud heirs to strengthen legal certainty, enhance the protection of inheritance rights, and promote consistency in judicial practice.